Workplace Health Protocols Compliance in the Food and Beverage Manufacturing Sector during the COVID-19 Pandemic in the Philippines - Serrano, Melisa R.; Marasigan, Mary Leian C. (Philippine Journal of Labor and Industrial Relations; Vol 39 (2022): Philippine Journal of Labor and Industrial Relations, 2023)
This research examines the implementation of COVID-19 workplace protocols in several Philippine food and beverage manufacturing (FBM) companies which are classified as essential economic sectors during the pandemic. It explores the areas of compliance and gaps in health and safety protocols introduced at that time and contribute to the literature on how workers and employers managed to operate the factories while reducing the risk of infection at work. The research data was collected through a small group survey of 12 union presidents in 11 food and beverage companies located in Luzon, Visayas and Mindanao and a focus group discussion involving union officers of the companies. The results suggest a mixed picture of compliance. COVID-19 protocols in masking, quarantine completion, entry checks at the gate, mass gathering and meeting restrictions, ventilation, provision of soaps and sanitation supplies, and ventilation were well-observed (90-100%). However, there was moderate observance (70-89%) of protocols pertaining to movement in aisles and stairways, daily sanitation and disinfection of work areas including toilets, isolation areas, open windows in shuttle services, presence of a COVID-19 Committee, PCR testing, and protocols for transporting symptomatic workers. Some disallowed practices were practiced such as the sharing of tables during mealtimes and talking to others or on the phone while inside shuttle services. The lack of safety officers and occupational safety and health (OSH) committees in many companies are seen as crucial factors affecting overall compliance to the health protocols.